2023
DOI: 10.3389/fneur.2023.1278508
|View full text |Cite
|
Sign up to set email alerts
|

Listening effort and fatigue among cochlear implant users: a scoping review

Cato Philips,
Laure Jacquemin,
Marc J. W. Lammers
et al.

Abstract: IntroductionIn challenging listening situations, speech perception with a cochlear implant (CI) remains demanding and requires high levels of listening effort, which can lead to increased levels of listening-related fatigue. The body of literature on these topics increases as the number of CI users rises. This scoping review aims to provide an overview of the existing literature on listening effort, fatigue, and listening-related fatigue among CI users and the measurement techniques to evaluate them.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Individuals with lower speech perception scores have been shown, in the present and other studies, to have lower working memory capacities (Tao et al, 2014;Kaandorp et al, 2017;Moberly et al, 2017b;Hillyer et al, 2019;O'Neill et al, 2019;El Ghazaly et al, 2021) and this may contribute to the higher levels of listening effort observed in CI users (Pérez et al, 2023;Philips et al, 2023). Although the mechanisms underlying the relationship between working memory and speech perception in CI users are not clear, one possibility may be related to individual differences in cognitive capacities.…”
Section: Relationships With Ciqol Communication Ssq Speech and Qualit...mentioning
confidence: 47%
“…Individuals with lower speech perception scores have been shown, in the present and other studies, to have lower working memory capacities (Tao et al, 2014;Kaandorp et al, 2017;Moberly et al, 2017b;Hillyer et al, 2019;O'Neill et al, 2019;El Ghazaly et al, 2021) and this may contribute to the higher levels of listening effort observed in CI users (Pérez et al, 2023;Philips et al, 2023). Although the mechanisms underlying the relationship between working memory and speech perception in CI users are not clear, one possibility may be related to individual differences in cognitive capacities.…”
Section: Relationships With Ciqol Communication Ssq Speech and Qualit...mentioning
confidence: 47%
“…Similarly, reliable clinical measures of listening effort are not yet available despite this being a common issue for patients with HL. 1 Lastly, current clinical measures fail to account for listeners' perception of details of the speech signal such as talker-specific features (eg, sex, age, accent, or dialect) or communicative intent (eg, emotional valence and verbal irony). 2 As a result, despite improvements in communication being a primary goal for most adult CI recipients, clinical measures of audibility and speech recognition fail to assess numerous communication abilities relevant to everyday life.…”
Section: Limitations Of Current Behavioral Measuresmentioning
confidence: 99%
“…After cochlear implantation, the available acoustic and spectro-temporal cues are limited, which would cause an increased listening effort [9]. This assumption was recently confirmed by a review of 24 studies that showed higher levels of listening effort in CI users when compared to normal-hearing controls using scales, questionnaires, and electroencephalogram measurements [29]. Nevertheless, the main factors leading to this difference still need to be clarified.…”
Section: Introductionmentioning
confidence: 96%
“…It is hypothesized that the technical parameters of cochlear implants greatly impact listening effort, more than age or cognitive factors do [ 9 ]. Other studies discussed the effects of cognitive factors such as working memory capacity or inhibitory control on listening effort [ 29 , 30 ] and found effects of aging on listening effort in CI users [ 31 ]. According to a study by Perrau et al, other variables, such as the duration of CI use and the age of onset of hearing loss, were not significantly related to listening effort [ 31 ].…”
Section: Introductionmentioning
confidence: 99%